Proses Persiapan Special Event Lomba Lukis Kolektif Pelajar Tingkat Nasional 2018 oleh CV Multi Arta Mayida - Maulidya Khairani; Tuty Herawati (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
This study aims to determine the process of preparing for events and pre-event management of the Lomba Lukis Kolektif Pelajar Tingkat Nasional 2018 organized by MAM EO. The method used in this study is a descriptive method where MAM EO is the object of research. This data collection technique is done through interviews, observation, documentation and literature study. The results of this study indicate that MAM EO applies pre-event management in the implementation of the Lomba Lukis Kolektif Pelajar Tingkat Nasional 2018 which are concept development, feasibility study, decision making, and implementation. The results of this study were MAM EO as the organizer of the Lomba Lukis Kolektif Pelajar Tingkat Nasional 2018 which was quite good at carrying out pre-event management even though there were some shortcomings. However, the event went according to the purpose of this event, which was to provide space for students to express their creativity and increase their potential in creating fine arts.